2023
DOI: 10.1101/2023.02.02.526657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling the Erythroblastic Island Niche of Dyserythropoietic Anaemia Type IV patients using Induced Pluripotent Stem Cells

Abstract: Congenital dyserythropoietic anaemia (CDA) type IV has been associated with an amino acid substitution, Glu325Lys (E325K), in the transcription factor KLF1. These patients present with a range of symptoms, including the persistence of nucleated red blood cells (RBCs) in the peripheral blood which reflects the known role for KLF1 within the erythroid cell lineage. The final stages of RBCs maturation and enucleation take place within the erythroblastic island (EBI) niche in close association with EBI macrophages… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…It was recently shown that proteins encoded by gene networks associated with mitochondrial biogenesis were upregulated in erythroid cells carrying the E325K mutation that is associated with Congenital Dyserythropoietic Anemia Type IV (Ferrer-Vicens et al, 2023). Proteomic analysis of macrophages carrying this pathogenic mutation will reveal whether comparable changes are associated with the EI niche using our recently developed model of this disease (May et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It was recently shown that proteins encoded by gene networks associated with mitochondrial biogenesis were upregulated in erythroid cells carrying the E325K mutation that is associated with Congenital Dyserythropoietic Anemia Type IV (Ferrer-Vicens et al, 2023). Proteomic analysis of macrophages carrying this pathogenic mutation will reveal whether comparable changes are associated with the EI niche using our recently developed model of this disease (May et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…RNA extraction was performed using the RNAeasy Mini Kit (74106, QIAGEN) following the manufacturer's instructions and cDNA was generated as previously described (May et al, 2023). Quantitative real time PCR reactions were performed on the Roche LightCycler ® 480 Instrument.…”
Section: Gene Expression Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…iPSC clones that had specifically integrated the iSAM cassette into the AAVS1 locus were validated by genomic PCR and sequencing (Figure S2A-B). The AAVS1 locus has been reported to be a "safe harbour" site that is resistant to epigenetic silencing and indeed, we had previously demonstrated that transgenes inserted into the AAVS1 locus under the control of the constitutively active CAG promoter were efficiently expressed both in undifferentiated and in differentiated iPSCs 20,[22][23][24] . However, after the iSAM line had been established and cultured under self-renewal conditions, we noted a dramatic reduction in the number of mCherry+ cells in undifferentiated iSAM iPSCs upon DOX induction, that we predicted to be due to transgene-silencing of the rTTA DOX-inducible cassette (Figure S3C).…”
Section: Development Of a Dox-inducible Dcas9-sam Activation System I...mentioning
confidence: 99%